Chinese and Global ADRs: The US Investor Experience. Issue 3 (3rd July 2021) - Bessembinder, Hendrik; Chen, Te-Feng; Choi, Goeun; Wei, K. C. John
Abstract : We study outcomes to ADR (American Depositary Receipt) investments between August 1954 and September 2020, with particular attention to ADRs associated with Chinese firms. Overall, ADRs improved investors' wealth by $1.03 trillion, with more than a third of this amount attributable to ADRs associated with Chinese firms. A value-weighted portfolio of ADRs associated with Chinese firms earned 14.1% per year since the first Chinese ADR was created in 1993, as compared with 9.9% per year for the overall US stock market over the same period. These data are relevant to current policy discussions focused on Chinese firms listed in the United States.